Unraveling the missing link of ENSO control over the Indian monsoon rainfall. Issue 19 (8th October 2015) - Dwivedi, Suneet; Goswami, B. N.; Kucharski, Fred
Abstract: Using long daily rainfall (113 years) data, clear evidence of modulation of the statistics of subseasonal active and break spells of the Indian summer monsoon rainfall (ISMR) by the El Niño–Southern Oscillation (ENSO) is unraveled. We show that during the El Niño (La Nina) years, the frequency of longer break (active) spells and shorter active (break) spells increases substantially, while the frequency of shorter breaks (active) and longer active (break) spells decreases compared to ENSO neutral years. It is shown that the large‐scale teleconnection through which ENSO weakens (strengthens) the ISMR through shortening (lengthening) of the length of rainy season (LRS) also creates a background for modulation of the statistics of subseasonal spells leading to a further reduction (increase) in the ISMR during El Niño (La Niña) years. Our findings indicate that the "statistics of subseasonal spells" is predictable, brightening the prospect of seasonal prediction of the ISMR. Key Points: A unified mechanism of ENSO control on South Asian monsoon rainfall is unraveled Monsoon "internal" variability is modulated by the ENSO and hence may be predictable Potential predictability of the ISMR is higher than previously estimated